Increasing the Added Value of Sambal Pecel Based on Local Wisdom Through Product Innovation and Flavor Diversification - Bayu Surindra; Tjetjep Yusuf Afandi; Zainal Arifin; Nina Widya Ningtyas; Mida Setyaningsih (CV. AFDIFAL MAJU BERKAH, 2026)
The management of sambal pecel as a traditional food product based on local wisdom in the Delta Sambiresik Permai 3 Housing Complex, Sambiresik Village, Gampengrejo District, Kediri Regency, still faces limitations in terms of flavor variety, production processes, and packaging, resulting in suboptimal added value and product competitiveness. This condition encourages the need for product innovation and flavor diversification accompanied by the application of appropriate technology and continuous assistance. The purpose of this activity is to increase the added value of pecel chili sauce through product innovation and flavor diversification based on local wisdom, as well as to improve the community's skills in a more hygienic and efficient production and packaging process. This community service activity was carried out over one semester through stages of observation, socialization, training, technology application, assistance and evaluation, as well as program sustainability. The results of the activity showed that the community was able to independently apply roasting techniques, develop flavor variations, and carry out modern packaging. In addition, the application of appropriate technology improved production efficiency and product quality consistency. This activity contributed to increasing the competitiveness of pecel sambal as an MSME product and supported the sustainability of local food businesses based on local wisdom.